Kajian Etnolinguistik terhadap Mitos dan Kearifan Lokal Lingkungan dalam Menjaga Ekosistem serta Pencegahan Bencana Alam di Kampung Adat Jalawastu - Muarif Husyandi; Fitri Novia Rahma; Eka Sri Pratiwi; Siti Muntapiroh; Muhammad Rinzat Iriyansah; Odien Rosidin (sarasvati, 2026)
This study examines the myths and local wisdom of the Jalawastu Traditional Village community through ethnolinguistic studies. The study aims to explain the forms of myths, taboos, oral traditions, and ecological values ​​contained in the culture of the Jalawastu community as an effort to protect the environment and prevent natural disasters. The method used in this study is descriptive qualitative with an ethnolinguistic approach. Research data were obtained through observation, interviews, and documentation of traditional leaders and the community of the Jalawastu Traditional Village in Brebes Regency, Central Java. The results show that the Jalawastu community possesses local knowledge that is passed down through generations through cultural language, as described below. The myth regarding the forbidden forest functions as a social control in maintaining forest sustainability and preventing environmental damage. The prohibition on wearing green clothing reflects a symbol of the community's respect for nature, which is considered to have a balance that must be maintained. The Ngasa ritual serves as a means to strengthen the harmonious relationship between humans, ancestors, and nature through the use of ritual language and cultural symbols. Oral traditions and the culture of mutual cooperation also play a role in passing on environmental conservation values ​​to the younger generation. Thus, the myths and local wisdom of the Jalawastu community serve not only as cultural heritage but also as a form of environmental preservation and disaster mitigation based on local culture.